Impacts of the Ukraine–Russia conflict on the global food supply chain and building future resilience - Dyson, Ellen; Helbig, Rachel; Avermaete, Tessa; Halliwell, Kate; Calder, Philip C.; Brown, Lynn R.; Ingram, John; Popping, Bert; Verhagen, Hans; Boobis, Alan R.; Guelinckx, Isabelle; Dye, Louise; et al. (Wiley, 2023)
The reverberations of the Ukraine–Russia conflict have been keenly felt in 2022 as the impacts of Russia's invasion of Ukraine quickly cascaded across the globe, significantly exacerbating existing pressures on global systems. The vulnerabilities of the global food system have been particularly laid bare with significant disruptions to food and fertiliser supply chains instigating profound shocks on global food supply – disproportionately affecting poorer and vulnerable populations of the Global South. The immediate concerns and potential solutions to the global impacts of the Ukraine–Russia conflict were recently discussed by a panel of industry, academic and civil society experts convened by the European branch of the International Life Sciences Institute, all of whom are authors of this manuscript. The key concerns: the reduced affordability of food – focussing on those most vulnerable to its effects; the socio-political implications of reduced food security; food safety; and nutrition security are all discussed in this Point de Vue. The authors voice the need for improved resilience to future shocks and stress on the food system.